Prevention of rice tungro virus infection by oils - A. ANJANEYULU2, M.K. SATAPATHY1 and (Indian Phytopathology, 2002)
An attempt has been made in the present study to know whether oils could prevent tungro virus infection and affect its leafhopper vector, Nephotettix virescens. Out of 11 plant and mineral oils tested under greenhouse conditions. Bayol 50 and Sunco 7N prevented virus infection significantly and caused vector mortality effectively. Sandoz, coconut and mustard oils were also relatively good. In further investigations, none of the oils was found to have persistence for long period in preventing tungro infection. However, the critical concentration at prevention of infection without any phytotoxicity was 2.0 per cent for Bayol 50 and Sandoz and 1.5 per cent for Sunco 7N oil.